Implementasi Pasal 106 Ayat (9) dan Sanksi Pasal 292 UU LLAJ terhadap Pelanggaran Bonceng Tiga - Dimas Hadijaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the implementation gap (Das Sein) against the normative provisions (Das Sollen) regarding the prohibition on riding a motorbike with more than one passenger (Bonceng Tiga/BOTI) as regulated in Article 106 Paragraph (9) of Law Number 22 of 2009 concerning Traffic and Road Transportation (LLAJ Law). The main problems studied are the factors underlying public non-compliance and the effectiveness of the role of the authorities in implementing criminal sanctions in the form of fines in Article 292 of the LLAJ Law. This study uses a normative legal research method with a statute approach and a conceptual approach. The secondary data analyzed are in the form of primary legal materials (LLAJ Law) and secondary (journals, books, study results). The results of the initial study indicate a significant gap between the prohibition norm (Das Sollen) and practice in the field (Das Sein). Public non-compliance is influenced by socio-economic factors (wanting to save time and costs), while the effectiveness of the maximum fine of IDR 250,000.00 (Article 292) is considered low because the nominal value does not create an adequate deterrent effect. In addition, inconsistent law enforcement also exacerbates ineffectiveness. Therefore, a revision of the legal substance and an increase in enforcement consistency are needed to optimize traffic safety guarantees.